FAKTOR-FAKTOR COLLABORATIVE GOVERNANCE DALAM PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN GAMBUT DI KABUPATEN BENGKALIS - Maylani, Tri; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Forest and peatland fires in Kabupaten Bengkalis are one of the environmental problems that often occur and are considered important so that it becomes the government's attention. Based on the source of the cause, forest and land fires can be grouped into two, namely natural amd forest firest that occur naturally and forest and land fires that occur as a result of human activities. Envorimental problems that are currently occuring which are quite severe problems are forest and land fires caused by irresponsible parties. The occurrence of forest and land fires in Kabupaten Bengkalis was caused in part by large activities in the framework of human land clearing, both for agricultural and plantation businesses supported by climatic condition and the presence of natural phenomena such as Elnio Southern Oscillation (ENSO). To overcome this problem, the government involves various parties such as the private sector and the community to be able to work together in overcoming the problem of forest and peat land fires called collaborative governance. The purpose of this study is to find out collaborative governance fakcotrs in the prevention of forest and peat land fires in Kabupaten Bengkalis. This study uses a type of qualitative research obtained through interview techniques, observation and documentation. The results of this study indicate that, the factors that hinder collaborative governance in preventing forest and peat land fires in Kabupaten Bengkalis are communication, regulations and work programs. Keywords : Factors of Collaborative Governance, Prevention of Forest and Peatland Fires